Evaluation of The Electrochemo-Mechanically Induced Stress in All-Solid-State Li-Ion Batteries. Issue 9 (18th May 2020) - Tian, Hong-Kang; Chakraborty, Aritra; Talin, A. Alec; Eisenlohr, Philip; Qi, Yue
Abstract : The mechanical degradation of all-solid-state Li-ion batteries (ASSLBs) is expected to be more severe than that in traditional Li-ion batteries with liquid electrolytes due to the additional mechanical constraints imposed by the solid electrolyte on the deformation of electrodes. Cracks and fractures could occur both inside the solid electrolyte (SE) and at the SE/electrode interfconce. A coupled electrochemical-mechanical model was developed and solved by the Finite Element Method (FEM) to evaluate the stress development in ASSLBs. Two sources of volume change were considered, namely the expansion/shrinkage of electrodes due to lithium concentration change and the interphase formation at the SE/electrode interface due to the decomposition of SEs. The most plausible solid electrolyte decomposition reactions and their associated volume change were predicted by density functional theory (DFT) calculations. It was found that the stress associated with a volume change due to solid electrolyte decomposition can be much more significant than that of electrode volumetric changes associated with Li insertion/extraction. This model can be used to design 3D ASSLB architectures to minimize their internal stress generation.